Differential Regulation of Tau Exon 2 and 10 Isoforms in Huntington's Disease Brain. (10th May 2023) - Petry, Serena; Nateghi, Behnaz; Keraudren, Rémi; Sergeant, Nicolas; Planel, Emmanuel; Hébert, Sébastien S.; St-Amour, Isabelle
Highlights: Huntington's disease is associated with deficits in MAPT alternative splicing. Higher tau exon 10 inclusion is a common trait of HD and consistently observed in both cortex and putamen. Lower tau exon 2 inclusion is specific to one region analyzed, the putamen, precedes tau hyperphosphorylation, and coincides with neurodegeneration. Our findings suggest isoform-specific functions of tau in HD neuropathology. Abstract: Huntington's disease (HD) is an inherited neurodegenerative disorder caused by an expansion of CAG repeats in the Huntingtin (HTT) gene. Accumulating evidence suggests that the microtubule-associated tau protein participates in the pathogenesis of HD. Recently, we have identified changes in tau alternative splicing of exons 2, 3 and 10 in the putamen of HD patients (St-Amour et al, 2018). In this study, we sought to determine whether tau mis-splicing events were equally observed in other brain regions that are less prone to neurodegeneration. Using Western blot and PCR, we characterized the relationship between MAPT splicing of exons 2, 3 and 10, tauopathy and Htt pathologies, as well as neurodegeneration markers in matching putamen and cortical samples from HD ( N  = 48) and healthy control ( N  = 25) subjects. We first show that levels of 4R-tau (exon 10 inclusion) isoforms are higher in both the putamen and the cortex of individuals with HD, consistent with earlier findings. On the other hand, higher 0N-tau (exclusion of exons 2 and 3) and lower 1N-tau (exclusion of exon 3) isoforms were seen exclusively in the putamen of HD individuals. Interestingly, investigated splicing factors were deregulated in both regions whereas exon 2 differences coincided with increased tau hyperphosphorylation, aggregation and markers of neurodegeneration. Overall, these results imply a differential regulation of tau exon 2 and exon 10 alternative splicing in HD putamen that could provide a useful biomarker or therapeutic target.